Cellulose-Based Nanofibers in Wound Dressing - Abdul Razak Masoud; Zeinab Jabbari Velisdeh; Mohammad Jabed Perves Bappy; Gaurav Pandey; Elham Saberian; David K. Mills (Biomimetics, 2025)
Wound dressings have a significant role in managing trauma-related injuries, chronic lacerations, as well as post-operative complications, by preventing infections and promoting tissue regeneration. Conventional methods using sutures and gauze often pose constraints in healing effectiveness and cost. Emerging materials, particularly cellulose-based nanofibers, offer a favorable choice due to their biodegradability, biocompatibility, and structural similarity to the extracellular matrix. Cellulose, being an abundant, naturally available biopolymer, forms the basis for modern materials for wound dressing. It is a very resourceful material due to its capability to be processed into films, fibers, and membranes with tailored properties. Surface modification of cellulose membranes with nanoparticles or bioactive compounds assists in enhancing the antimicrobial properties and supports sustained drug release, essential in chronic wound infections. Electrospinning and other modern fabrication techniques allow for controlling the fiber morphology and drug-delivery characteristics. This review highlights the properties, fabrication techniques, surface functionalization, and biomedical applications of cellulose-based materials in wound care. With increasing demand for effective and cost-effective wound treatments, cellulose nanofibers stand out as a sustainable, multifunctional platform for cutting-edge wound dressings, offering improved healing, reduced scarring, and potential for amalgamation with several drug delivery and tissue engineering approaches.